2012
DOI: 10.1029/2012ja017592
|View full text |Cite
|
Sign up to set email alerts
|

Ionogram signatures of large‐scale wave structure and their relation to equatorial spread F

Abstract: [1] Observations of signatures of the large-scale wave structure (LSWS) and subsequent development of equatorial spread F (ESF) by using data from a newly installed digital ionosonde at Trivandrum (8.5 N; 77 E; 0.5 N magnetic dip latitude) are presented. The LSWS signatures are observed using the ionograms with echo directions. The 'satellite' traces are shown as echoes from oblique directions, when an upwelling (associated with LSWS) is not directly over the ionosonde location. When an upwelling is centered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Additional evidence regarding upwelling presence comes from two ionogram signatures, namely multi-reflected echoes (MREs) (Tsunoda 2009;Thampi et al 2012;Tsunoda et al 2013) and satellite traces (STs) (Abdu et al 1981;Tsunoda 2008;Thampi et al 2012). The finding that MREs appear most often around the time of SS E (Tsunoda et al 2015) is consistent with the finding that upwellings are amplified during the PSSR; in fact, the maximum in PSSR rate is centered more or less about SS E (Tsunoda 2009;Tsunoda et al 2015).…”
Section: Ionogram Signaturessupporting
confidence: 75%
See 2 more Smart Citations
“…Additional evidence regarding upwelling presence comes from two ionogram signatures, namely multi-reflected echoes (MREs) (Tsunoda 2009;Thampi et al 2012;Tsunoda et al 2013) and satellite traces (STs) (Abdu et al 1981;Tsunoda 2008;Thampi et al 2012). The finding that MREs appear most often around the time of SS E (Tsunoda et al 2015) is consistent with the finding that upwellings are amplified during the PSSR; in fact, the maximum in PSSR rate is centered more or less about SS E (Tsunoda 2009;Tsunoda et al 2015).…”
Section: Ionogram Signaturessupporting
confidence: 75%
“…Enhancement is possible, when reflection occurs from concave isodensity contours, such as those associated with an upwelling (Tsunoda 2009;Thampi et al 2012). Enhancement should be strongest, when the radius of curvature of the reflecting surface is approximately equal to the height of reflection.…”
Section: Ionogram Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESF appeared to the east at 1730 UT (Figure f); it appeared to recede in the ionogram taken at 1745 UT and was gone by 1800 UT (Figure h). Strong MREs [ Tsunoda , 2009; Thampi et al ., ] were observed at 1845 UT, which could be interpreted in terms of upwelling presence in the vicinity. Eastward drifting ESF structures have been reported before, for example, by Argo and Kelley [, Figure 6] and by Tsunoda [, Figure 3].…”
Section: Conjunctions: Striations Upwellings and Patchesmentioning
confidence: 92%
“…Other than scanning radars (e.g., ALTAIR), the only instrument capable of providing information about spatial ionospheric structure (without horizontal transport) is an ionosonde [Tsunoda, 2005]. Toward this end, we have shown that multi-reflected echoes (MREs) are ionogram signatures for LSWS [Tsunoda, 2009;Thampi et al, 2012]. Figure 4 presents an example of MREs in an ionogram taken at Kwajalein.…”
Section: Multi-reflected Echoes: a Means For Monitoring Lsws Presencementioning
confidence: 99%